Analysis of Teachers' and Students' Perception of the Use of Metaphors in Biology - Anna Fitri Hindriana; Ina Setiawati; Zaenal Abidin; Amarina Atâ€™haya; Lilis Karlina (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to investigate teachers' and students' perceptions of the use of metaphor in learning biology including the effectiveness of and the interest in using metaphor in learning biology. The investigation builds on assumption that metaphor is a potential method to alter the way teachers and students respond to abstract and complex concepts. The data in this study was obtained qualitatively using the triangulation method involving Focus Group Discussion (FGD) with an expert group and individual interviews. The instrument utilized in this study is a discussion guide and an interview guide containing open questions which later was transcribed and analyzed. The respondents of this study are 30 biology teachers and 71 senior high school students from three districts in West Java, Indonesia.Â  The result shows that teachers and students respond positively to the use of metaphors in learning biology concepts. In addition, teachers express that metaphor helps in delivering abstract and complex biology concepts as well as developing creativity in teaching. Meanwhile, students express that metaphor has the potential to help them understand biology concepts, increase interest in learning biology, and build relevance to the concept.